Acacetin from Traditionally Used Saussurea involucrata Kar. et Kir. Suppressed Adipogenesis in 3T3-L1 Adipocytes and Attenuated Lipid Accumulation in Obese Mice - Liou, Chian-Jiun; Wu, Shu-Ju; Chen, Li-Chen; Yeh, Kuo-Wei; Chen, Chih-Ying; Huang, Wen-Chung (Frontiers in Pharmacology, 2017)
Acacetin, a flavone that can be isolated from the Saussurea involucrata plant, has anti-tumor and anti-inflammatory properties that ameliorate airway hyperresponsiveness in asthmatic mice. This study investigated whether acacetin has anti-adipogenic effects in 3T3-L1 adipocytes and whether it regulates the inflammatory response in adipocytes and macrophages. It also investigated whether acacetin ameliorates lipid accumulation in high-fat diet- (HFD) induced obese mice. Differentiated 3T3-L1 cells were treated with acacetin. The glycerol levels in the culture medium were measured, and the expression of proteins and genes involved in adipogenesis and lipolysis were assayed by Western blot and real-time PCR, respectively. Inflammatory cytokine signaling pathway activity was assessed in macrophages that were treated with acacetin and cultured with differentiated medium from 3T3-L1 cells. Intraperitoneal injections of acacetin were administered to HFD-induced obese mice twice a week for 10 weeks. Acacetin significantly increased the levels of glycerol in the culture medium and significantly inhibited lipid accumulation in adipocytes. Acacetin reduced the expression of adipogenesis-related transcription factors, including the expression of the CCAAT/enhancer-binding protein; it also increased sirtuin 1 expression and AMPK phosphorylation in adipocytes. In macrophages cultured with differentiated media from 3T3-L1 adipocytes, acacetin reduced the levels of inflammatory mediators and the activity of the mitogen-activated protein kinase and NF-κB pathways. In obese mice, acacetin reduced both body weight and visceral adipose tissue weight. These results demonstrate that acacetin inhibited adipogenesis in adipocytes and in obese mice. Acacetin also reduced the inflammatory response of macrophages that were stimulated with differentiated media from 3T3-L1 cells.